No full stops in India - "Tully, Mark" (New Delhi, 1991)
A series of stories which reveal the many faces of India - its beauty and terrible poverty; its corruption and the strength and dignity of its poor; and its yearning for modernity and the richness of its ancient cultures.
Keywords: Social Conflict